中国视网膜中央动脉阻塞临床诊疗专家共识 Expert Consensus on Clinical Diagnosis and Treatment of Central Retinal Artery Occlusion in China - 中国研究型医院学会神经眼科专业委员会，陕西省研究型医院学会神经眼科专业委员会 Neuro-Ophthalmology Society, Chinese Research Hospital Association; Neuro-Ophthalmology Society, Shaanxi Research Hospital Association (Zhongguo cuzhong zazhi)
视网膜中央动脉阻塞（central retinal artery occlusion，CRAO）是一种血管神经眼科急症，发病后可导致患者单眼视力急骤下降甚至丧失，显著增加急性缺血性血管事件（如卒中、急性心肌梗死）、死亡和眼部新生血管等发生风险。CRAO被视为急性缺血性卒中的一种特殊类型，临床诊疗仍存在争议，尤其是不同专业背景的医师对CRAO的临床诊疗存在显著差异。因此，制定并推行符合我国国情的CRAO临床诊疗共识显得尤为迫切和必要。我们通过参考国际CRAO管理说明和实践模式，进行系统性文献检索，结合我国国情，制定了《中国视网膜中央动脉阻塞临床诊疗专家共识》（以下简称共识）初稿。经过核心专家组多次审议修订后，最终形成此共识。本共识围绕CRAO的流行病学、解剖及发病机制、危险因素、临床表现、辅助检查、分型、自然病程、视力恢复影响因素、首诊科室、快速评估、治疗（包括保守治疗、对因治疗、静脉溶栓和动脉内溶栓）、血管事件风险（包括急性缺血性血管事件、死亡）、继发眼部新生血管风险与治疗、二级预防和科学管理等方面进行详细且全面的阐述，旨在提高我国CRAO的整体管理水平。临床医师应用此共识时，建议根据患者的实际病情和诊疗中心的具体情况进行个体化诊疗。所有医疗人员要始终坚持“时间就是视觉”理念，尽快将CRAO患者转诊至就近的、具有CRAO诊疗能力的综合卒中中心进行诊治，争取最大限度地改善患者视力，减少并发症发生风险。 Abstract: Central retinal artery occlusion (CRAO) is a vascular neuro-ophthalmic emergency that causes a rapid decline or even loss of vision in one eye after onset. It also significantly increases the risk of acute ischemic vascular events (such as stroke, and acute myocardial infarction), death, and ocular neovascularization (ONV). CRAO is regarded as a special type of acute ischemic stroke, and there are still controversies in its clinical diagnosis and treatment, especially significant differences among physicians with different professional backgrounds. Therefore, it is particularly urgent and necessary to formulate and implement the consensus on the clinical diagnosis and treatment of CRAO that aligns with China’s national circumstances. By referring to international guidelines for CRAO management and practice patterns, conducting systematic literature searches, and combining with China’s national circumstances, we formulated the draft of the Expert Consensus on Clinical Diagnosis and Treatment of Central Retinal Artery Occlusion in China (hereinafter referred to as the consensus). After the core expert group deliberated and revised many times, this consensus was finally formed. This consensus provides a detailed and comprehensive explanation of CRAO’s epidemiology, anatomy and pathogenesis, risk factors, clinical manifestations, auxiliary examinations, classification, the natural course of the disease, factors affecting vision recovery, first contact departments, rapid assessment, treatment (including conservative treatment, etiological treatment, intravenous thrombolysis, and intra-arterial thrombolysis), risk of vascular events (including acute ischemic vascular events and death), risk and treatment of secondary ONV, secondary prevention and scientific management, in order to improve the overall management level of CRAO in our country. When clinicians apply this consensus, it is recommended to provide individualized diagnosis and treatment based on the actual condition of the patient and the specific circumstances of the clinic. All medical staff should always adhere to the concept that “time is vision” and refer CRAO patients to the nearest comprehensive stroke center with CRAO diagnosis and treatment capabilities as soon as possible, striving to maximize the improvement of patients’ vision and reduce the risk of complications.